2020
DOI: 10.1111/jsr.13096
|View full text |Cite
|
Sign up to set email alerts
|

Caring for the carers: Advice for dealing with sleep problems of hospital staff during the COVID‐19 outbreak

Abstract: Hospital staff are at the frontline in the COVID‐19 outbreak. The stressors they experience may induce sleep problems in a population already at risk. Sleep deprivation, long shifts and insomnia in hospital staff have been associated with individual, organizational and public health hazards. These include increased risk of mental and somatic disorders, altered immune responses, medical errors, misunderstandings, drowsy driving and burnout. In March 2020, the World Health Organization called for providing acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 88 publications
4
29
0
2
Order By: Relevance
“…As the most severe public health crisis in the recent half-century, COVID-19 pandemic has affected emotion, body, cognition, and behavior among hospital workers ( Williams et al., 2014 ). Many studies had found significant emotional and physical reactions to this crisis in hospital workers, such as depression, anxiety, PTSD, insomnia, and somatic symptom ( Ho et al., 2020 ; Kisely et al., 2020 ; Luo et al., 2020 ; Ballesio et al., 2020 ). Various sociodemographic factors were found associated to emotional and physical symptoms among hospital workers in this study such as lower educational background, female, and single, which were consistent with the findings in previous studies ( Kisely et al., 2020 ; Zhang et al., 2020 a; Luo et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the most severe public health crisis in the recent half-century, COVID-19 pandemic has affected emotion, body, cognition, and behavior among hospital workers ( Williams et al., 2014 ). Many studies had found significant emotional and physical reactions to this crisis in hospital workers, such as depression, anxiety, PTSD, insomnia, and somatic symptom ( Ho et al., 2020 ; Kisely et al., 2020 ; Luo et al., 2020 ; Ballesio et al., 2020 ). Various sociodemographic factors were found associated to emotional and physical symptoms among hospital workers in this study such as lower educational background, female, and single, which were consistent with the findings in previous studies ( Kisely et al., 2020 ; Zhang et al., 2020 a; Luo et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, the impairment occurred ( Zhang et al., 2020 a; Fava et al., 2019 ). Negative emotions (anxiety, guilt, and loneliness) were reported to activate cognitive mechanisms and result in poor self-rated health and high self-rated infected possibility ( Ballesio et al., 2020 ). However, compared with emotional and physical outcomes, epidemic-related attitudes and behaviors had showed a close relationship to stress and support in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Было выявлено влияние тревоги, вины и одиночества на негативную оценку собственного здоровья и профессиональной успешности. Все это способствовало деморализации и уверенности в неизбежности инфицирования [20].…”
Section: Introductionunclassified
“…Further, there is a complete lack of research on the effects of the lockdown on circadian rhythms in humans (Bryson 2020;Erren and Lewis 2020). However, many studies have been conducted to evaluate the impact of COVID-19 pandemic on anxiety disorders (Huang and Zhao 2020; Sher 2020), depressive symptoms (Huang and Zhao 2020), sleep quality (Huang and Zhao 2020;Qi et al 2020;Stanton et al 2020), and mid-sleep timings (Sinha et al 2020;Majumdar et al 2020), although a majority of the studies is speculative and suggestive (Chen et al 2020;Yadav et al 2020;Mônico-Neto et al 2020;Ballesio et al 2020;Becker and Gregory 2020).…”
Section: Introductionmentioning
confidence: 99%